The Effectiveness of Online Learning in Increasing Student Productivity - Lutfiana Nisarohmah; Medina Chodijah (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the relationship between the effectiveness of online learning and student productivity. This research method is qualitative through literature study with content analysis approach. The discussion of this research includes the conditions of online learning, the effect of online learning on students, and the effectiveness of online learning. This study concludes that the effectiveness of online learning can be achieved through the use of learning media that students enjoy and are familiar with. The emergence of a feeling of pleasure while learning has a great influence on students' understanding and activeness so that they can increase their productivity.